2019
DOI: 10.5334/gjgl.720
|View full text |Cite
|
Sign up to set email alerts
|

Language disintegration under conditions of severe formal thought disorder

Abstract: On current models of the language faculty, the language system is taken to be divided by an interface with systems of thought. However, thought of the type expressed in language is difficult to access in language-independent terms. Potential interdependence of the two systems can be addressed by considering language under conditions of pathological changes in the neurotypical thought process. Speech patterns seen in patients with schizophrenia and formal thought disorder (FTD) present an opportunity to do this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
4
1
Order By: Relevance
“…However, let us observe that both null pronouns and null 3Person referential pronouns were less significantly correlated with FTD, thought disorder, as measured by PANSS P2 scores ([N]: r = 0.419; p = 0.007, and [N3P+R]: r = 0.402; p = 0.010). Hence, in tension with previous observations that language issues pattern together with FTD in SZ [ 30 , 51 ], our results indicate that atypical overuse of null pronouns is significantly associated with positive symptoms in general, but less so with FTD.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, let us observe that both null pronouns and null 3Person referential pronouns were less significantly correlated with FTD, thought disorder, as measured by PANSS P2 scores ([N]: r = 0.419; p = 0.007, and [N3P+R]: r = 0.402; p = 0.010). Hence, in tension with previous observations that language issues pattern together with FTD in SZ [ 30 , 51 ], our results indicate that atypical overuse of null pronouns is significantly associated with positive symptoms in general, but less so with FTD.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we conclude that, due to methodological issues, our samples are not informative about pronominal anomaly in SZ, but it is important to notice that the SZ groups produced significantly more null 3Person referential pronouns in WK narratives, and more null 3Person referentially anomalous pronouns in all narrative types across samples. Tovar et al—as far as we know, the only study that investigated the use of null pronouns in patients with SZ—reported more errors in the use of null referential pronouns as compared to overt pronouns [ 51 ]. Our finding converges with that of Tovar et al’s with respect to that.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence that schizophrenia leads to semantic and pragmatic impairments. It has been reported, for instance, that schizophrenic patients overuse expressions with implicit, generic or ambiguous reference (Harvey;Weintraub;Neale, 1982, Rodriguez-Ferrera;McCarthy;McKenna, 2001, Hinzen;Sheehan, 2015), have difficulties with definiteness, ineffectively using indefinite DPs for new information and definite DPs for old information, as well as difficulties with third person pronominal coreference (Rochester;Martin 1979, Harvey;Weintraub;Neale, 1982, Chaika;Lambe, 1989, Çokal et al, 2018, Sevilla et al, 2018, Tovar et al, 2019. It has also been shown that these speakers have difficulties integrating contextual information David, 1998, Kuperberg et al, 2006, being more influenced by lexical meaning (Chapman;Chapman;Miller, 1964), in addition to difficulties using information shared with the interlocutor (Champagne -Lavau;…”
Section: Introductionmentioning
confidence: 99%